EDUKASI ILMU WARIS DALAM UPAYA MEMBANGUN KELUARGA DAN MASYARAKAT YANG HARMONIS BAGI WARGA CISEENG, KABUPATEN BOGOR - Roni Hidayat; Karimulloh; Afrizal Tw; Aya Yahya; Raka Radityo; Muhammad Farhan; Hasby Alamsyah; Latanza Wakaramaka (LPPM Universitas Abdurrab, 2025)
One of the social conflicts that often occurs within families is the dispute over the distribution of inheritance. Many cases have resulted in damaged family relationships due to inheritance issues. In various regions, including Ciseeng, Bogor Regency, many people still lack understanding of the rules for inheritance distribution according to Islamic law. Therefore, the community service team from YARSI University carried out a counseling program entitled